Re-envisioning Islamic Higher Learning Through the Jabalul Hikmah Curriculum: A Transdisciplinary Framework for Global Innovation - Fauzi, Fauzi; Fakhruddin, Asef Umar; Suharsiwi, Suharsiwi; Syauqi, M. Labib (Kharisma: Jurnal Administrasi dan Manajemen Pendidikan, 2025)
This study explores the transformative orientation of the Jabalul Hikmah Curriculum as an emerging model for re-envisioning Islamic higher learning in Indonesia. Amid global demands for integrative, future-oriented educational systems, Islamic universities face the challenge of reconstructing their curriculum to remain intellectually relevant and socially impactful. The purpose of this article is to analyse how the Jabalul Hikmah Curriculum offers a transdisciplinary framework for global innovation, positioning it as a significant contribution to contemporary Islamic higher education discourse. A qualitative–phenomenological approach was employed, combining content analysis with field-based inquiry. Data were collected from key stakeholders at UIN Prof. K.H. Saifuddin Zuhri Purwokerto and triangulated with insights from UIN Maliki Malang, UIN Sunan Kalijaga Yogyakarta, and UIN Syarif Hidayatullah Jakarta as comparative benchmarks. The analytical procedures followed a systematic approach to data reduction, data display, and conclusion verification. The study adopts Evelina M. Vicencio’s curriculum development framework, which consists of designing, planning, implementing, and evaluating. The findings reveal that the Jabalul Hikmah Curriculum represents a substantive curricular innovation, integrating Islamic epistemology, human development, and contemporary scientific paradigms within a unified architecture. Its alignment with the national Merdeka Belajar–Kampus Merdeka (MBKM) policy demonstrates both relevance and adaptability. The study’s implications highlight the curriculum’s potential to serve as a global model for Islamic higher education reform, offering a replicable pathway toward holistic, future-ready intellectual formation.